Psychosocial Interventions for Pain Management in Advanced Cancer Patients: a Systematic Review and Meta-analysis - Warth, Marco (Curr Oncol Rep, 2020)
PURPOSE OF REVIEW: This systematic review and meta-analysis aimed to synthesize the evidence on the effects of psychosocial interventions on pain in advanced cancer patients. RECENT FINDINGS: The included studies investigated the effects of relaxation techniques, cognitive-behavioral therapy, music therapy, mindfulness- and acceptance-based interventions, and supportive-expressive group therapy. Overall, we found a small, but significant effect on pain intensity (d = − 0.29, CI = − 0.54 to − 0.05). Effect sizes were highly heterogeneous between studies. We did not find evidence for the superiority of any of the intervention types. However, psychosocial interventions may be more effective if they specifically targeted pain distress as the primary outcome. SUMMARY: Although findings were mixed, psychosocial interventions can be recommended to complement comprehensive care to alleviate pain in patients facing an advanced or terminal stage of the disease. Future research should develop innovative interventions tailored specifically for pain relief.